Determinants and short‐term physiological consequences of PHA immune response in lesser kestrel nestlings. Issue 7 (8th May 2014) - Rodríguez, Airam; Broggi, Juli; Alcaide, Miguel; Negro, Juan José; Figuerola, Jordi
ABSTRACT Individual immune responses are likely affected by genetic, physiological, and environmental determinants. We studied the determinants and short‐term consequences of Phytohaemagglutinin (PHA) induced immune response, a commonly used immune challenge eliciting both innate and acquired immunity, on lesser kestrel (Falco naumanni) nestlings in semi‐captivity conditions and with a homogeneous diet composition. We conducted a repeated measures analyses of a set of blood parameters (carotenoids, triglycerides, β‐hydroxybutyrate, cholesterol, uric acid, urea, total proteins, and total antioxidant capacity), metabolic (resting metabolic rate), genotypic (MHC class II B heterozygosity), and biometric (body mass) variables. PHA challenge did not affect the studied physiological parameters on a short‐term basis (<12 hr), except plasma concentrations of triglycerides and carotenoids, which decreased and increased, respectively. Uric acid was the only physiological parameter correlated with the PHA induced immune response (skin swelling), but the change of body mass, cholesterol, total antioxidant capacity, and triglycerides between sessions (i.e., post—pre treatment) were also positively correlated to PHA response. No relationships were detected between MHC gene heterozygosity or resting metabolic rate and PHA response. Our results indicate that PHA response in lesser kestrel nestlings growing in optimal conditions does not imply a severe energetic cost 12 hr after challenge, but is condition‐dependent as a rapid mobilization of carotenoids and decrease of triglycerides is elicited on a short‐term basis. J. Exp. Zool. 321A: 376–386, 2014. © 2014 Wiley Periodicals, Inc.